Reminder letter of findings and observation on submitted design and meeting with related designer of BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding reminder letter of findings and observation on submitted design and meeting with related designer of BRAC University new campus project.